Individual Work of Foreign Students in Professional Training - Олексенко, Вячеслав Михайлович (Educological discourse, 2014)
The results of the research in increasing the efficiency of individual work of foreign students in their professional training are highlighted. The key role of the studactive classes in this process is defined.